Conductivity-difference-enhanced DC dielectrophoretic particle separation in a microfluidic chip. Issue 6 (28th February 2022) - Li, Deyu; Yu, Weicheng; Zhou, Teng; Li, Mengqi; Song, Yongxin; Li, Dongqing
Abstract : Conductivity-difference-enhanced DC dielectrophoretic particle separation in a microfluidic chip. Two immiscible electrolyte solutions with different conductivities in microchannels. Abstract : A conductivity-difference-based method for increasing dielectrophoretic (DEP) force for particle separation in a microfluidic chip is presented in this paper. By applying a direct-current (DC) voltage across two immiscible electrolyte solutions with a conductivity difference, an enhanced electric field gradient is generated at the liquid–liquid interface. Theoretical analysis based on equivalent circuit theory found that the gradient of the electric field squared increases with the decrease in the conductivity ratio of the two liquids (main channel to the side channel). As a result, the particle separation distance (an indicator of DEP force) increases with the decrease in the conductivity ratio, which is both numerically predicted and experimentally verified. Numerical simulations also show that the separation distance increases with the increase in the magnitude of the electric field and the decrease in the width of the orifice. The method presented in this paper is simple and advantageous for increasing DEP force without applying higher DC voltages or fabricating smaller orifices.